Capacity factor estimation of variable-speed wind turbines considering the coupled influence of the QN-curve and the air density. (15th September 2019) - Song, Dongran; Yang, Yinggang; Zheng, Songyue; Tang, Weiyi; Yang, Jian; Su, Mei; Yang, Xuebing; Joo, Young Hoon
Abstract: This paper proposes a systematic method that precisely estimates the capacity factor (CF) of the variable-speed wind turbine (WT) by considering the coupled influence of the turbine operation constraints and the air density. To do so, the WT's operation is defined by introducing the QN-curve (denoting the generator torque versus rotor speed), and the influence of different QN-curves on the power production is analysed while considering the influence of the air density. Then, a practical power-curve model considering the constraint of the QN-curve is derived for the WT. Following that, the formulation and the procedure of CF estimation are presented. Lastly, the presented CF estimation approach is applied into an industrial WT while considering the wind sites with four different altitudes. Finally, the application results show the capabilities of the proposed approach in evaluating the CF under the coupled influence of the QN-curve constraint and the air density. Meanwhile, comparing the proposed approach to four empirical approaches demonstrates that the CF estimation based on empirical models has considerable deviations to the results of the presented model under different site altitudes. Furthermore, among the four empirical models, the CF estimations from the quadratic and the linear models present the least deviations to those by the proposed model at the sites with low altitude and high altitude, respectively. Highlights: A precise approach to estimate the CF of the variable-speed WT is proposed. Coupled influence of the turbine operation and air density on the CF is included. Proposed approach is applied to an industrial WT under different air density. Considerable deviations are found between the empirical and proposed estimations. CF is reduced following the decreasing air density.